Magnetic hydroxypropyl chitosan functionalized graphene oxide as adsorbent for the removal of lead ions from aqueous solution. Issue 9 (19th February 2016) - Wang, Yaoguang; Yan, Tao; Gao, Liang; Cui, Limei; Hu, Lihua; Yan, Liangguo; Du, Bin; Wei, Qin
Abstract: Magnetic hydroxypropyl chitosan/graphene oxide (MHCGO) composites have been synthesized and employed as adsorbent for removal of lead ions from aqueous solution. X-ray powder diffraction, Fourier transform infrared spectrum, and scanning electron microscope showed that the MHCGO composites were fabricated successfully. The effects of adsorbent dosage, pH, and contact time on the adsorption of lead ions have been discussed, and the optimal adsorption conditions have been acquired. The results indicated that the adsorption of lead ions on MHCGO was dependent on pH with the optimum pH nearly 5.5. The adsorption process was fairly quick and the time to reach adsorption equilibrium is 100 min. The adsorption kinetics could be described by the pseudo-second-order model very well. Adsorption data fitted well with Freundlich model. The effect of temperature on lead ions adsorption was studied and was shown to be spontaneous.